Bacteriological studies for Kranji catchment - Ong, Cheryl Li Ying. (2010)
A study investigating the bacterial concentrations in Kranji Catchment and the factors affecting the bacterial die-off rates was carried out. The scope of the study involved field water sampling as well as an attenuation study of E. coli. A first-order attenuation model was constructed to establish the effect of solar radiation on the inactivation of E. coli and determine if the bacteria die-off substantially before reaching Kranji Reservoir. Field sampling comprised comparison of the bacteriological levels in KC02 was done with reference to past studies conducted. IDEXX Colilert® Most-Probable-Number (MPN) method was used to quantify the bacterial levels for both total coliform and E. coli.